2020
DOI: 10.3390/app10207327
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Radar and Gauge Rainfall Data Sources on the Analysis of Spatial Distribution of Traffic Accidents and Rainfall Events

Abstract: The records of 24,797 traffic accidents (9039 involving fatalities or severe injury) during rainy conditions from 2007 to 2017 in Seoul, South Korea, were used to analyze the spatial distribution of the traffic accidents and rainfall events based on radar and gauge rainfall data. According to the spatial correspondence analysis between rainfall distribution and accident locations for localized and stratiform rain events, radar data in a two-dimensional grid (250 by 250 m) of 10 min temporal resolution benefite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Tobin et al [ 15 ] estimated the relative risk of crashes during rain using a matched-pair analysis in Kansas for 1995–2014. Yoon et al [ 16 ] collected data of traffic accidents during rainy conditions from 2007 to 2017 in Seoul, South Korea. Rainstorms can lead to a series of secondary disasters, such as flash floods, landslides, mudslides, house collapses, and traffic and communication interruptions, which can bring serious harm to the national economy and people’s lives and property.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tobin et al [ 15 ] estimated the relative risk of crashes during rain using a matched-pair analysis in Kansas for 1995–2014. Yoon et al [ 16 ] collected data of traffic accidents during rainy conditions from 2007 to 2017 in Seoul, South Korea. Rainstorms can lead to a series of secondary disasters, such as flash floods, landslides, mudslides, house collapses, and traffic and communication interruptions, which can bring serious harm to the national economy and people’s lives and property.…”
Section: Introductionmentioning
confidence: 99%
“…Rainstorms can lead to a series of secondary disasters, such as flash floods, landslides, mudslides, house collapses, and traffic and communication interruptions, which can bring serious harm to the national economy and people’s lives and property. Previous studies have mainly focused on the accidents caused by rainstorms [ 14 , 15 , 16 ], but they have failed to conduct a deep analysis of the causes, consequences, and prevention measures of these accidents. Preliminary hazard analysis (PHA) [ 17 , 18 ], fault tree analysis (FTA) [ 19 , 20 ], and bow-tie models [ 21 , 22 ] are widely used to identify the causes, consequences, and prevention measures for fatal accidents, and the results have shown that these methods can obtain accurate accident data and reduce the risk of accidents.…”
Section: Introductionmentioning
confidence: 99%